2016
DOI: 10.1097/coc.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Nodal Ratio in Patients Undergoing Adjuvant Chemoradiotherapy After Curative Resection for Ampullary Cancer

Abstract: Adjuvant chemoradiotherapy after curative resection can achieve a long-term survival rate in patients with ampullary cancer. Nodal ratio and histologic differentiation are independent prognostic factors for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Considering that the prognostic cut-off value for ampullary cancer ranges from 0.1 to 0.2, 15,16,19,24 the calculated cut-off value of 0.07 is consistent with previous reports. Based on the results of the ASCOT trial, 10 S-1 would be a standard treatment for adjuvant chemotherapy after curative surgery; however, in cases with an LNR ≥ 0.07, the introduction of more effective regimens would be required to improve the prognosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Considering that the prognostic cut-off value for ampullary cancer ranges from 0.1 to 0.2, 15,16,19,24 the calculated cut-off value of 0.07 is consistent with previous reports. Based on the results of the ASCOT trial, 10 S-1 would be a standard treatment for adjuvant chemotherapy after curative surgery; however, in cases with an LNR ≥ 0.07, the introduction of more effective regimens would be required to improve the prognosis.…”
Section: Discussionsupporting
confidence: 90%
“…Several prognostic factors have been reported in ampullary cancer after surgical resection, including age, lymph node metastasis, number of lymph node metastases, LNR, pancreatic and duodenal invasion, stage, tumor size, gross appearance, perineural invasion, histological type, and lymphovascular invasion. [18][19][20][21][22][23][24] This study's multivariate analysis for OS identi ed sex and lymph node metastasis as independent prognostic factors (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, several predictors of LNM in resected AVC have been described including number of retrieved LNs, ratio of positive LNs/retrieved LNs, number of metastatic LNs (based on UICC N stage classi cation), and location of regional LNs (pancreatic head or except for pancreas head) [5,6,[18][19][20]. Matui et al reported that regional LNM, except to the pancreatic head region, was associated with poor prognosis, comparable to that of patients with M1-stage [21].…”
Section: Discussionmentioning
confidence: 99%
“…LNR has been confirmed as a prognostic factor of AC patients, but no uniform cutoff threshold for LNR has been established. Kim et al retrospectively analyzed 71 patients with AC who underwent adjuvant chemotherapy after radical resection and found that LNR > 0.15 was an independent risk factor for OS (10). In an analysis of 212 AC patients who received radical surgery in Taiwan, LNR > 0.056 indicated poor DFS and OS (11).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported the rate of lymph node metastasis (LNM) ranges from 20% to 50% (1). Despite many clinicopathologic characters are associated with prognosis for AC patients, LNM is still one of the most crucial risk factors (1,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%